Chain Epistemologis Mufasir Pesantren Terhadap Interpretasi Aḥrūf Muqaṭṭa’ah Perspektif Historis - Mukhlisin, Yusuf; Ittaqi Tafuzi (Bulletin of Indonesian Islamic Studies, 2023)
The debate on interpretation of aḥrūf muqaṭṭa'ah is still debated by commentators to this day. Some scholars do not interpret aḥrūf muqaṭṭa'ah with the argument that these verses are sirr al-Qur'ān and mutasyabihat verses. Others argue that aḥrūf muqaṭṭa'ah must have a meaning that needs to be explored and interpreted as an effort to show the aspect of guidance (huda) in the Qur'an. This study does not attempt to clash the two groups above. The author focuses on the historical aspects of the meaning of aḥrūf muqaṭṭa'ah and its epistemology. Through Abdul Mustaqim's periodization mapping model, it can be concluded that the interpretation of aḥrūf muqaṭṭa'ah has been made since the early era of Islam (Prophet Muhammad's phase). In this phase, the interpretation of aḥrūf muqaṭṭa'ah, apart from coming from insiders, was also carried out by outsiders of Muslims. Meanwhile, from the perspective of Abid al-Jabiri's epistemology, there was almost no significant epistemological development from the early to the modern phase. Each period continues to use the bayani epistemology model, with one of the characteristics of the interpretation model through history being the dominant current. As for the form of interpretation of aḥrūf muqaṭṭa'ah, it can be categorized into three models of history, language analysis, and numerical formulation (ḥisāb al-jummal). These three models also influence the interpretations of Indonesian mufasirs.